A new hybrid teaching learning based optimization -extreme learning machine model based intrusion-detection system - Alsudani, Mustafa Qahtan; Abbdal Reflish, Salah; Moorthy, Kohbalan; Adnan, Myasar Mundher (Elsevier Ltd, 2023)
Currently, effective Intrusion-detection systems (IDS) still represent one of the important security tools. However, hybrid models based on the IDS achieve better results compared with intrusion detection based on a single algorithm. But even so, the hybrid models based on traditional algorithms still face different limitations. This work is focused on providing two main goals; firstly, analysis based on the main methods and limitations of the most-recent hybrid model-based on intrusion detection, secondly, to propose a novel hybrid IDS model called TLBO-ELM based on the Firefly algorithm and Fast Learning Network.